The #FeesMustFall protest: when the camp(u)s becomes the matrix of a state of emergency - Kamga, Gerard Emmanuel Kamdem (Acta Academica: Critical views on society, culture and politics, 2019)
The paper examines the state’s response to students’ claim for free education that has rocked South African tertiary institutions since 2015. These responses have been characterised by the enforcement of a de facto state of emergency materialised by an extreme securitisation/militarisation of campuses and other public spaces, resulting in human/student rights and the rule of law being brought to a standstill. The paper further discusses the background to the #FeesMustFall protest and attempts to understand why the crisis was addressed only more than two years after it erupted. The article proceeds by looking into the aftermath of the fees must fall campaign characterised by an escalation of security mechanisms which succeeded in turning the campuses into camps where fact and law are merged into one another and where a state of emergency has lost its exceptional character and became the new normal.